KONTRIBUSI AGROFORESTRI TERHADAP PENDAPATAN PETANI DIDESA SAYOANG KECAMATAN BACAN TIMUR KABUPATEN HALMAHERA SELATAN - Palihema, Wiwin; Hadun, Ramli; Abullatif, Zauzah; Umasugi, Buhari; Kurniawan, Andy; Sapsuha, Yusri (Jurnal Pertanian Khairun, 2024)
Agroforestry plays an important role in improving people's livelihoods and preserving natural forests. Agroforestry land use management is needed to improve the socio-economic development of farmers. Therefore, it is important to carry out research by analyzing how much farmers' income in Sayoang Village is and how much agroforestry contributes to farmers' income because this commodity is used as the main source of productive family income. This research was carried out in Sayoang Village, East Bacan District, South Halmahera Regency. The tools used in this research were, Camera, laptop and office stationery Meanwhile, the material is a questionnaire. Data collection methods in research consist of interviews, observation, questionnaires and literature study. The population in the research was the farming community in Sayoang Village, Regency with a sample of 41 agroforestry farmers. Data analysis was carried out using a quantitative descriptive method by analyzing how much farmers earn and how much agroforestry contributes to farmers' income. results from agroforestry products, namely forestry plants, agriculture, fisheries and livestock. The income of farmers in Sayoang Village, using an agroforestry system ranges between Rp. 887,885–Rp. 3,923,944/month or between Rp. 10,654,500 – Rp. 47,087,333/year. The contribution of agroforestry to farmers' income in Sayoang Village, East Bacan District is very large, namely 87.94%.